Basic biology - Realuyo, Zenaida M. (Makati City : MINDSHAPERS CO,. INC., 2006)
This textbook was designed to provide a non-laboratory general biology course for students enrolled in non-science courses such as Bachelor's degree in Arts, Education, Business and Commerce, Law and other related courses. This author had long years of experience in teaching biological science to Filipino students who do not aspire to become involved in the sciences but interested in science because we live in a world governed by scientific principles and concepts.
Unit 1. Introduction -- Unit 2. The Cell -- Unit 3. Energy Transformation -- Unit 4. Diversity of Life -- Unit 5. The Human Body -- Unit 6. Heredity and Environment.
Includes bibliographical references, and index.
Keywords: BIOLOGY